Proof and ascertainment of customary law - Bekker, JC; van der Merwe, IA (Southern African Public Law, 2023)
In the light of the constitutional recognition of customary law as one of the sources of our law, this article explores whether the Law of Evidence Amendment Act 45 of 1988 is still relevant as a basis for its ascertainment during litigation. The questions that are addressed deal with the status of customary law, whether courts may take judicial notice thereof or whether it should be proved, and on what basis? In short, the question is whether the constitutional recognition of customary law has made any difference to prior evidentiary rules or practice with regard to its application in court.